ENT 530 Social Media Portfolio: Chibby Shop / Nurul Hazirah Ahmad Kabir - Ahmad Kabir, Nurul Hazirah (2021)
The chocojar product is named Chocojerr. Chocojerr is a snack and dessert food under types of food business. The owner of the business is Nurul Hazirah binti Ahmad Kabir. The name of this page of business company is ChibbyShop. This business starts on 23 October 2020 as the date of registration of the business on Go-eCommerce. This product is a dessert food. Chocojerr is basically kind of dessert because the combination of chocolate and bubble rice. The chocolate and bubble rice are mixed together and we can eat at anywhere and anytime. In addition, the chocolate that were used is the premium chocolate and also give many benefits to us. The founder of this product is a Malaysian. In addition, this chocojar product became trendy and famous until today. Many people demand for this sweet dessert to satisfy their craving. This is because this food product is easier to get with affordable price and it is also suitable for all age. That’s make this product still have it’s own customer until now. This product also available at Facebook Page ChibbyShop. ChibbyShop have provided about the product information and advertisement to promote business. By this way, customer will easily reach me by WhatsApp and Facebook to place order.